Składniowe wyznaczniki przynależności kulturowej - Moroz, Andrzej (Investigationes Linguisticae, 2013)
The starting point for the discussion is the hypothesis of Richard E. Nisbett about differences of thinking and communication systems between people of the East and the West. It is significant that these differences have specific linguistic markers, on syntactic level as well. Therefore, the aim of this text is an attempt to answer the question: how the syntactic subsystem of the contemporary Polish language is located in indicated dichotomy. It appears that the answer is not easy and requires consideration of many aspects of this problem. The final conclusion, however, tends to the statement that the Polish syntax is the complex unit and includes the features of both communication systems – east and west – but we can notice the gravity to the West.